Implementation of an extended simulator for the HF channel on a multi-DSP board - Van der Perre, L; Van de Capelle, A; Ade, M; Lauwereins, R (7th International Conference on High Frequency Radio Systems and Techniques, 1997)
An extended model for the HF channel is being implemented on a multi-DSP board. As a channel model, an extension of the Watterson (1970) model is proposed, adjusted to encompass both frequency dependencies to serve as a basis for testing wideband modems, and structural variations of the propagation parameters to subject modems using adaptive algorithms and equalisers to proper test conditions. The implementation of the model on a multi-DSP board is accomplished using `Grape' (Graphical Rapid Prototyping Environment). The hardware implementation has to cope both with the complex channel model and the wide bandwidths of the signals that have to be treated. The use of general purpose DSP boards enables a modular and flexible design, which is kept as close to the physical phenomena as possible. There is an option for a division in subbands in order to simplify the processing of wideband signals.